NNLOPS accurate associated HZ production with H → b b ¯ $$ H→ b\overline{b} $$ decay at NLO - William Astill; Wojciech Bizoń; Emanuele Re; Giulia Zanderighi (Journal of High Energy Physics, 2018)
Abstract We present a next-to-next-to-leading order (NNLO) accurate description of associated HZ production, followed by the Higgs boson decay into a pair of b-quarks treated at next-to-leading order (NLO), consistently matched to a parton shower (PS). The matching is achieved by performing reweighting of the HZJ-MiNLO events, using multi-dimensional distributions that are fully-differential in the HZ Born kinematics, to the NNLO results obtained by using the MCFM-8.0 fixed-order calculation. Additionally we include the gg → HZ contribution to the discussed process that appears at the O α s 2 $$ \mathcal{O}\left(α_s^2\right) $$ . We present phenomenological results obtained for 13 TeV hadronic collisions.